ABOUT NON-NEWTONIAN OIL FILTRATION FEATURES IN THE AREA OF BYTKIV FIELD'S WELLS DRAINAGE - Качмар, Юрій Дмитрович; Цьомко, Володимир Васильович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Strengthening the anomalous properties of oil due to decreasing reservoir pressure at the late stage of field development after depression creation leads to the formation zone with destructed structure of reservoir oil around of the well that proceed to zone with undisturbed structure. Dual-zone model of the oil flow to the well was applied and the conditional radius of fracture of structure under conditions of increase gradient of depression over gradient of boundary shearing stress of oil was determined. Increasing the efficiency of carrying out of hydraulic fracturing of formation was achieved only after the creation of cracks outside the fracture zone structure.